Robust design of a multi‐floor isolation system. Issue 4 (5th January 2018) - Anajafi, Hamidreza; Medina, Ricardo A.
Summary: A multi‐floor isolation (MFI) technique can provide a building with inherent dynamic vibration suppressors through decoupling different portions of floors masses from the superstructure. This paper evaluates the seismic effectiveness and robustness of the MFI technique using a test‐bed 20‐story building. First, a parametric study approach is utilized to optimize MFI configurations with different isolated mass ratios ( IMR s) and different number of isolated floor subsystems (IFSs). The response quantity to be optimized is the sum of root‐mean‐square interstory drift responses of the superstructure under a stochastic excitation. The sensitivity of the seismic performance of the optimally designed MFI configurations with respect to uncertainties in the properties of the superstructure, IFSs, and the ground excitation is evaluated. Simulation results illustrate that with the presence of these uncertainties, the effectiveness of the optimally designed MFI configurations with low and high IMR s (e.g., 5% and 90%) is significantly impaired, whereas configurations with intermediate IMR s (e.g., 50%) exhibit a relatively stable performance. Evaluation of the optimal placement of IFSs along the building height, when the number of IFSs is limited, reveals that placing the IFSs at top stories can lead to a near‐optimal system in terms of the spatial distribution of IFSs. A genetic algorithm is used to design a robust system for a selected configuration with top 10 IFSs and an IMR of 50%. The robust design is performed via minimizing the maximum deviation with respect to the design root‐mean‐square interstory drift response when the design parameters vary within a given uncertainty range.